Collaboration between patient organisations and a clinical research sponsor in a rare disease condition: learnings from a community advisory board and best practice for future collaborations. Issue 12 (16th December 2020) - Roennow, Annelise; Sauvé, Maureen; Welling, Joep; Riggs, Robert J; Kennedy, Ann Tyrrell; Galetti, Ilaria; Brown, Edith; Leite, Catarina; Gonzalez, Alex; Portales Guiraud, Alexandra Paula; Houÿez, François; Camp, Rob; et al.
Abstract : Introduction Transparent collaborations between patient organisations (POs) and clinical research sponsors (CRS) can identify and address the unmet needs of patients and caregivers. These insights can improve clinical trial participant experience and delivery of medical innovations necessary to advance health outcomes and standards of care. We share our experiences from such a collaboration undertaken surrounding the SENSCIS ® clinical trial (NCT02597933 ), and discuss its impact during, and legacy beyond, the trial. Summary We describe the establishment of a community advisory board (CAB): a transparent, multiyear collaboration between the scleroderma patient community and a CRS. We present shared learnings from the collaboration, which is split into three main areas: (1) the implementation and conduct of the clinical trial; (2) analysis and dissemination of the results; and (3) aspects of the collaboration not related to the trial. 1. The scleroderma CAB reviewed and provided advice on trial conduct and reporting. This led to the improvement and optimisation of trial procedures; meaningful, patient-focused adaptations were made to address challenges relevant to scleroderma-associated interstitial lung disease patients. 2. To ensure that results of the trial were accessible to lay audiences and patients, written lay summaries were developed by the trial sponsor with valuable input from the CAB to ensure that language and figures were understandable. 3. The CAB and the CRS also collaborated to co-develop opening tools for medication blister packs and bottles. In addition, to raise disease awareness among physicians, patients and caregivers, educational materials to improve diagnosis and management of scleroderma were co-created and delivered by the CAB and CRS. Conclusions This collaboration between POs and a CRS, in a rare disease condition, led to meaningful improvements in patient safety, comfort and self-management and addressed information needs. This collaboration may serve as a template of best practice for future collaborations between POs, research sponsors and other healthcare stakeholders.